1978
DOI: 10.1079/bjn19780015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the gut microflora and of dietary fibre on epithelial cell migration in the chick intestine

Abstract: 1. The renewal of the intestinal mucosal epithelium has been investigated in germ-free and conventional chicks given a practical chick diet and a low- and high-fibre diet, using tritiated thymidine to label the nuclei of mucosal cells undergoing division. 2. Villus height, crypt depth and number of mitoses in the crypt were generally, although not always significantly, greater for conventional chicks than for germ-free chicks at all sites investigated in the intestine, and all became progressively lower from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The addition of wheat bran to a diet had no effect on the rate of renewal of intestinal epithelium in conventional and germ-free chicks (Rolls et al 1978 More recently Tasaki and Sakwai (1969), showed that the relationship between urinary nitrogen and nitrogen intake of cockerels is curvilinear; the same relationship was found for urinary energy. ln presenting a theoretical basis for extending the TME bioassay methodology to minerals, Sibbald (1982) Returning to the possible effects of diet on F-E + U.E, Shires et al (1919) (1919) and Kessler and Thomas (19'f 9) support this conclusion.…”
Section: Metabolic Plus Endogenous Energymentioning
confidence: 59%
“…The addition of wheat bran to a diet had no effect on the rate of renewal of intestinal epithelium in conventional and germ-free chicks (Rolls et al 1978 More recently Tasaki and Sakwai (1969), showed that the relationship between urinary nitrogen and nitrogen intake of cockerels is curvilinear; the same relationship was found for urinary energy. ln presenting a theoretical basis for extending the TME bioassay methodology to minerals, Sibbald (1982) Returning to the possible effects of diet on F-E + U.E, Shires et al (1919) (1919) and Kessler and Thomas (19'f 9) support this conclusion.…”
Section: Metabolic Plus Endogenous Energymentioning
confidence: 59%
“…The suggested explanation was that in the jejunum the presence of micro-organisms results in increased turnover of epithelial cells (Rolls et al 1978) and in the liver of CV birds there is greater activity due to the need to metabolize bacterial end-products. Skeletal muscle is not in close association with micro-organisms, so it seemed important to the better understanding of host-microflora interrelations to investigate whether or not the presence of the gut microflora affects muscle protein turnover.…”
mentioning
confidence: 99%
“…On the contrary, Shurson et al (1990) reported that germ-free pigs had longer ileal and duodenal villi but shorter jejunal villi compared to their conventional counterparts. In the germ-free chicken (Rolls et al, 1978) and rodents (Komai and Kimura, 1979;Ishikawa et al, 1986;Meslin et al, 1992) villus length was reported to decrease progressively along the small intestine from the duodenum to the distal ileum. This regional response was suggested to be the result of regional variation in microbial species diversity and abundance.…”
Section: Discussionmentioning
confidence: 99%